Pengaruh Kegiatan Pemasaran di Media Sosial, Ulasan Elektronik dari Mulut ke Mulut, dan Penyokong Selebriti terhadap Niat Membeli dengan Kesadaran Merek sebagai Variabel Intervening (Studi Kasus pada Scarlett Whitening di Kalangan Generasi Z Kota Semarang - Dewi Amartya; Suryono Budi Santosa (Faculty of Economics and Business | Universitas Diponegoro, 2022)
This study aims to analyze the effect of social media marketing activities, electronic word of mouth, celebrity endorsement, and brand awareness on purchasing intention making (a study on Scarlett Whitening in Generation Z Semarang City), as well as to find out the variables that most influence purchasing intention Â so that it can be an overview in making strategies to increase purchasing intention for Scarlett Whitening. This research was conducted for residents residing in Semarang. The number of samples in this study were 114 respondents with the criteria being active Instagram users that knowing and had visited @scarlett_whitening before who are 17 â€“ 27 years old and domiciled in Semarang City. The data collection method used in this study is through a questionnaire. This study uses Structural Equation Modeling (SEM) as an analytical tool. The results of this study indicate that social media marketing activities has a positive and significant effect on brand awareness, electronic word of mouth has a positive and significant effect on brand awareness, celebrity endorsement has a positive and significant effect on brand awarenes, brand awareness has a positive and significant effect on purchase intention. In other hand, social media marketing activities, electronic word of mouth, and celebrity endorsement have no effect on purchase intention.